SYSTEMATIC REVIEW OF SOCIETAL AND HEALTH SYSTEM COST OF DENGUE IN LATIN AMERICA - Perpétua Palha Dias Parente, Mirian; Teixeira de Siqueira Filha, Noemia; Cortes, Fanny; Itria, Alexander; Bosco Siqueira Jr, Joao; Maria Turchi Martelli, Celina (Revista de Patologia Tropical / Journal of Tropical Pathology, 2018)
Aim: to conduct a systematic literature review on dengue costs in Latin America, comparing study methodologies, disease costs and the economic impact of dengue in different countries. Methods: the literature search was carried out in the following electronic databases: MEDLINE/PubMed, EMBASE and LILACS, for the period between 2004 and 2014. To make comparisons possible, the costs identified in the selected studies were converted to local currency values, adjusted to the consumer price index (2014) and converted to purchasing power parity (PPP). Results: 728 publications were identified in databases and 13 papers were selected for analysis. Nine of the thirteen studies were conducted from a societal perspective and three from a health system perspective. In most studies, indirect costs accounted for the largest percentage of total outpatient costs. In contrast, for hospitalized patients, direct medical costs showed the highest percentages. The economic impact of dengue was estimated at I$ 3.2 billion per year, ranging from I$ 1.4 to I$ 5.9 billion, when including the six sub-regions of the Americas. Conclusion: dengue represents a high cost for Latin American society and health system. Studies varied in terms of cost methodology (cost items included, such as direct medical and non-medical and indirect costs, and cost analysis) and the different epidemiological periods in which research was carried out (endemic and/or epidemic).